Legal Analysis of Division of Joint Property in Divorce Based on the Civil Code - Murdiani Anas, Andi Indah Zahra; Muhdar, Muhammad Zulkifli; Alam, Syamsul (Qawanin Jurnal Ilmu Hukum, 2025)
This study aims to analyze the legal provisions related to the division of joint property in divorce. In addition, this study also evaluates the implementation of these rules in judicial practice and the obstacles faced in resolving joint property disputes. The research method used is normative juridical with a statutory approach and analysis of court decisions. Data were obtained through a literature study of relevant legal regulations, doctrines, and jurisprudence. The results of the study indicate that the Civil Code regulates the division of joint property equally between husband and wife, unless there are certain reasons that affect the division. Meanwhile, the Marriage Law refers to the laws that apply to each party, both customary law, religion, and other regulations. In practice, there are still inconsistencies in the application of these rules in court, especially related to differences in judges' interpretations and the influence of the legal system adopted by the parties. This study recommends harmonization of the provisions in the Civil Code and the Marriage Law in order to create legal certainty. In addition, it is important for couples to understand the benefits of a marriage agreement as an effort to prevent disputes in the division of joint property after divorce.